2012
DOI: 10.1016/j.mod.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster p24 trafficking proteins have vital roles in development and reproduction

Abstract: p24 proteins comprise a family of type-I transmembrane proteins of ~24kD that are present in yeast and plants as well as metazoans ranging from Drosophila to humans. These proteins are most commonly localized to the endoplasmic reticulum (ER)-Golgi interface and are incorporated in anterograde and retrograde transport vesicles. Little is known about how disruption of p24 signaling affects individual tissue function or whole animals. Drosophila melanogaster express nine p24 genes, grouped into four subfamilies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…Some new genes that regulate development are very young, existing in only one or a few species. For example, p24-2 exists in a single species, D. melanogaster , and has a vital role in development in this species 47 , even though the gene is absent in the close sibling species Drosophila simulans, Drosophila mauritiana and Drosophila sechellia 46 . These observations suggest that these species-specific and lineage-specific genes have rapidly become indispensable components of the genetic control of development.…”
Section: The Roles Of New Genes In Developmentmentioning
confidence: 99%
“…Some new genes that regulate development are very young, existing in only one or a few species. For example, p24-2 exists in a single species, D. melanogaster , and has a vital role in development in this species 47 , even though the gene is absent in the close sibling species Drosophila simulans, Drosophila mauritiana and Drosophila sechellia 46 . These observations suggest that these species-specific and lineage-specific genes have rapidly become indispensable components of the genetic control of development.…”
Section: The Roles Of New Genes In Developmentmentioning
confidence: 99%
“…Constitutive silencing of p24‐2 was found to cause pupal lethality of flies, indicating an essential role of this gene in development (Chen et al ., ). Ubiquitous reduction in p24‐2 levels in adults did not affect female fecundity but decreased male fertility in Drosophila (Saleem et al ., ); however, the underlying mechanism remains unclear. Wolbachia affects many transport‐associated molecules in male hosts (Zheng et al ., ; Yuan et al ., ; Wu et al ., ) and thus affects spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Kank, a gene that affects muscle tendon development, has been shown to be differentially expressed downstream of dsx (Lebo et al 2009), suggesting AI regulation in the sex determination pathway in virgins only. p24-1 has sex-specific expression (Boltz et al 2007) and has been shown to play a role in the neural signaling involved in female egglaying defects and reproductive behavior (Saleem et al 2012). In addition, zCOP is involved in lipid storage and regulation of lipid droplets (Guo et al 2008b) consistent with regulatory changes in lipid metabolism after mating in the fruit fly.…”
Section: Environmental Effects On Allelic Imbalancementioning
confidence: 99%